DEMİR EKSİKLİĞİ ANEMİSİNDE İRİSİN VE FABP4 ROLÜNÜN ARAŞTIRILMASI - SELMANOĞLU, AHMET (Fırat Üniveristesi, 2016)
Demir eksikliği anemisi (DEA) gelişmekte olan ülkelerde sık karşılaşılan önemli bir sağlık problemidir. Klinik özellikleri arasında büyüme ve gelişme geriliği ile termoregülasyonda bozulma yer alır. İrisin (Ir) bej yağ dokusunu enerji ve ısı sağlayan kahverengi yağ dokusuna dönüştürür. İrisin kas kitlesiyle pozitif korelasyon gösteren bir miyokindir. Yağ asidi bağlayıcı proteinler (FABPs) hücre içi yağ asitlerinin taşınmasında rol oynar Yağ asidi bağlayıcı protein 4 (FABP4) olgun adipositlerde bulunur. Demir eksikliği anemisinde kas dokusu azaldığından, Ir düzeyinde azalma, rölatif yağ dokusu arttığından FABP4 düzeyinde artış olması beklenebilir. Çalışmamızla, DEA'nde Ir ve FABP4 düzeylerinin araştırılması ve bu şekilde DEA ve semptomları üzerindeki etkilerinin değerlendirilmesi amaçlandı. Çalışmaya (DA: Demir deposu boş, n: 20], DE: Serum demiri azalan, n: 20], DEA: Demir eksikliği anemisi gelişen, n: 20] ve Kontrol: Demir belirteçleri normal olan, n: 20]) toplam 80 olgu alındı. Hasta ve kontrol grubu olgularından tedaviden hemen önce, tedavinin 3. ayında olmak üzere toplam 2 defa kan ve idrar örnekleri alındı. Çalışmamızda tüm gruplarda serum Ir düzeyleri tedavi sonrası artış gösterdi. Demir eksikliği anemisinde halsizlik ve fiziksel aktivitede azalma gibi semptomlar Ir düşüklüğüne bağlı olabilir. Demir eksikliği anemisinde termoregülasyonda bozulma ve normal derecelerde bile üşüme hissi gibi semptomlar bildirilmiştir. Termoregülasyon bozukluğunun olası sebebi azalan Ir düzeyi olabilir. Çünkü Ir, UCP-1 (Uncoupling protein 1) proteinlerini arttırarak ATP sentezi yerine; ısı enerjisi üretimine yol açmaktadır. Serum ve idrar FABP4 değerleri, tedavi öncesi ve sonrası kontrol değerlerinden farklı bulunmamıştır. Serum ve idrar FABP4 değerleri, istatistiksel anlamlı olmasa da DEA' nde kontrolden daha yüksek seviyelere ulaşmıştır. Demir eksikliği anemisinde görülen gelişme geriliği insülin düzeyi azalmasıyla ilgilidir. FABP4 insülin direncini artırmaktadır. Demir eksikliği anemisinde insülin düzeyinde azalma ile FABP4 düzeyinde artmanın neden olduğu insülin direnci gelişme geriliğini açıklayabilir. Anahtar Sözcükler: Demir eksikliği anemisi, İrisin, FABP4

Iron Deficiency Anemia (IDA) is a noteworthy health problem, frequently encountered in developing countries. Among its clinical presentations are growth retardation, developmental delay and disorder of thermoregulation. The irisin transforms the beige adipose tissue into the brown energy and heat dissipating adipose tissue. It is a myokine that exhibits positive correlation with the muscle mass of iris. The fatty acid-binding proteins (FABPs) play a role in facilitation of intracellular fatty acids. The fatty acid-binding protein 4 (FABP4) is found in mature adipose tissues. In the case of iron deficiency anemia, an increase in the FABP4 level can be expected due to the loss of muscle tissue together with a degradation of Ir level and increment of relative adipose tissue. By means of this study, we aim to conduct a research on Ir and FABP4 levels and thus evaluate the effects of the aforementioned on IDA and related symptoms. A total of 80 cases (DA: Empty iron store, n: 20], DE: Low serum iron, n: 20], DEA: Developing iron deficiency anemia, n: 20] and Control: Normal iron indicators, n: 20]) were included in the study. Blood and urine samples from the abovementioned cases, both the patient and control groups, were taken twice; first, prior to the commencement of the treatment and the latter, on the 3rd month of the ongoing treatment. Within the scope of our study, both groups exhibited an increase in post-treatment serum Ir levels. Symptoms of iron deficiency anemia such as fatigue and decline in physical activity may be connected with the low Ir levels. Symptoms such as disorder of thermoregulation and cold sensations event at normal body temperatures were also reported in relation with iron deficiency anemia. A possible reason for the disorder of thermoregulation can be the decreasing Ir level. This is due to the fact that Ir conduces to the generation of thermal energy rather than the synthesis of ATP by enhancing UCP-1 (Uncoupling protein 1) proteins. A difference between the serum and urine FABP4 ratios and pre- and post-treatment control ratios was not reported. Even though statistically insignificant, the serum and urine FABP4 ratios achieved higher levels in IDA compared to the control group. The growth retardation, encountered with in iron deficiency anemia, is related with the decreasing insulin levels. FABP4 increases the resistance of insulin. In consideration of IDA, the decrement in insulin levels and the insulin resistance caused by the increasing FABP4 level could explain the growth retardation. Key Words: Iron deficiency anemia, İrisin, FABP4
The research on the roles of irisin and FABP4 in iron deficiency anemia
Keywords: Hematoloji; Çocuk Sağlığı ve Hastalıkları